Proceedings of the 19th ACM Symposium on Virtual Reality Software and Technology 2013
DOI: 10.1145/2503713.2503733
|View full text |Cite
|
Sign up to set email alerts
|

Scalable optical tracking for navigating large virtual environments using spatially encoded markers

Abstract: In this paper we present a novel approach for tracking the movement of a user in a large indoor environment. Many studies show that natural walking in virtual environments increases the feeling of immersion by the users. However, most tracking systems suffer from a limited working area or are expensive to scale up to a reasonable size for navigation.Our system is designed to be easily scalable both in working area and number of simultaneous users using inexpensive off-the-shelf components. To accomplish this, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…When natural images features are not a strict requirement for the application at hand, a set of artificial features can be introduced consisting of bar codes, QR codes, ArUco (Garrido-Jurado et al, 2014) or alternatively designed custom markers (Jorissen et al, 2014). Maesen et al (2013) and Podkosova et al (2016) have laid the groundwork for this approach with their fundamental research on large-area tracking, but evaluation has only been performed in very constrained environments.…”
Section: Related Workmentioning
confidence: 99%
“…When natural images features are not a strict requirement for the application at hand, a set of artificial features can be introduced consisting of bar codes, QR codes, ArUco (Garrido-Jurado et al, 2014) or alternatively designed custom markers (Jorissen et al, 2014). Maesen et al (2013) and Podkosova et al (2016) have laid the groundwork for this approach with their fundamental research on large-area tracking, but evaluation has only been performed in very constrained environments.…”
Section: Related Workmentioning
confidence: 99%
“…However, real walking requires sufficiently large physical spaces, which are almost always in different (usually smaller) sizes and shapes from the corresponding virtual spaces (unless the latter are designed from the former, as in [Simeone et al 2015]). Techniques such as physical props [Cheng et al 2015], warped spaces [Suma et al 2012;Vasylevska et al 2013], and redirected walking [Razzaque et al 2001;Maesen et al 2013;Zmuda et al 2013;Nescher et al 2014] have been proposed to reconcile the virtual and physical worlds, and behavior studies have indicated that limited amounts of space distortion can be acceptable for VR navigation [Steinicke et al 2008;Zhang and Kuhl 2013;Nilsson et al 2014;Bruder et al 2015]. However, existing methods are not general enough to map between a given pair of virtual and physical environments.…”
Section: Real Walkingmentioning
confidence: 99%
“…This results in a system that can be easily extended to larger areas, but as a trade-off only returns a pose relative to the starting position and not to a fixed predefined coordinate system. Maesen et al [18] recently proposed a new system that encodes the position of the dots using De Bruijn codes and decodes the positions with the help of cross-ratios. This allows the tracker, contrary to their earlier system, to estimate the pose in relation to a predefined coordinate system.…”
Section: Related Workmentioning
confidence: 99%